THE AIA RECRUITING FILM. - Broder, Bertram (The Accounting Review, 1954)
A critical shortage of certified public accountants is one of the big problems facing the American Institute of Accountants (AIA) today. The first major effort in this recruiting drive is a 16 mm. 21 minute monochrome sound film, "Accounting–The Language of Business," which was officially released on December 15, 1953. The script was carefully scrutinized by members of the AlA personnel and public relations committees with at least one AlA representative being present during the whole process of production to assure the correctness of details. The film is introduced by a brief scene in which a father asks a friend who is a certified public accountant to explain possibilities of public accounting as a career for his son who is about to graduate from high school. The final episode deals with tax work. The AlA feels the film will have served its purpose if it conveys a generally favorable impression of the certified public accountant and his standing in the community. This film has even greater public relations value than recruiting value.